Role of Environmental Photocatalysts and Organic Matter on the Degradation and Toxicity of Metformin Hydrochloride - Rifat Khan; Jaqueline Regalado; Malsha Indeewari Kanaththage; Praveen L. Patidar; Gayan Rubasinghege (Toxics)
Metformin is the preferred first-line treatment for non-insulin-dependent diabetes mellitus, known for its benefits in cancer suppression, weight loss, and antiketogenic activity. It is a leading drug regarding mass distribution, and its high solubility in water leads to its significant accumulation in surface and groundwater. While some studies have explored its degradation products and toxicological consequences, none have specifically examined the impact of individual natural minerals and their mechanisms leading to these degraded compounds. Our investigation focuses on understanding the mineralogical effects of different photocatalysts and organic matter while assessing acute toxicity through cell viability tests on human cell lines. We utilized a custom-built reactor system containing metformin hydrochloride, photocatalysts, and organic matter under oxidizing conditions to explore the formation of new degraded compounds. We assessed the acute toxicity of both metformin hydrochloride and the resulting chemical mixture on kidney and liver cell lines using the colorimetric MTT cell viability assay. Despite the abundance of surface functional groups in organic humic acid, only solar energy-driven catalysts were found to effectively break down this widely used medication. Comparative analysis of metformin hydrochloride and its degraded residues indicates a toxic effect on liver cells. Our experiments contribute to understanding the environmental fate of metformin and pave the way for further biochemical investigations to identify toxicological mechanisms.